Designing a Graph Anonymization Framework for Secure Packet Transmission in the IP Over Ethernet LAN - Ganguli, R; Roy, S (International Journal of Computer Sciences and Engineering, 2025)
Ethernet Local Area Network (LAN) has become almost omnipresent today. Ethernet has scored over its competitor LAN technologies because of its simplicity, ruggedness and low cost as well as, the advantages it enjoyed owing to its early entry into the LAN market. Despite many research work and development efforts in the area of data communication’s security, the importance of internal local area network LAN security is still underestimated. Ethernet LAN has always been known to be an insecure technology. There is no way in the Ethernet LAN protocol to check the authentication or message integrity. Intruder can hack the IP packet header and create packets with false IP addresses or MAC addresses. In this paper we discuss about the design of a secured packet transport scheme in the IP over Ethernet LAN (IPEL) based on graph anonymization approach. To ensure secure communication, the identity of IP packet source and destination needs to be hidden from intruder. In our proposed scheme each host in the IPEL encrypts the header part of IP packet using graph anonymization algorithm and forwards to the next node. On receiving the packet host performs decryption using graph de-anonymization algorithm to read the packet header. This approach of securing IP packet header offers good scalability, possibly low cost and also promises a reasonable level of security in the IPEL